Pengaruh Trainer Dan Metode Pelatihan Terhadap Kinerja : Studi Pada Peserta PT. Pelita Training Centre Makassar - Abdul Safrin D Talli; Sulaiman (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Training relied on the fact that labour will require the knowledge, skill, and ability to expand to work eminently whereas efficacy program training can be influenced by the ability of the trainer and the training method. This research is done as a means to know its influence is trainers and training methods on performance (Study at competitor PT. Pelita Training Centre Makassar). Data was obtained by propagating etiquette to 40 training competitors, which is determined using the method of convenience sampling. Data obtained is to be done by the test of data quality before being analyzed to use the doubled method regress, test the partial, and determination. Results of the research show that the variable of trainer and training method has an effect positive and significant to the performance of training competitor in Pelita Training Centre Makassar, where variable trainer owns the stronger correlation to the performance of training competitor